2015
DOI: 10.1142/s0192415x15500068
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Inhibits the Fenton Reaction by Enhancing Electron Transfer from Fe2+ to Dissolved Oxygen

Abstract: Sho-saiko-to is an herbal medicine that is known to have diverse pharmacological activities and has been used for the treatment of various infectious diseases. Here, we examined the effects of baicalin, a compound isolated from Sho-saiko-to, and the effects of the iron chelator quinolinic acid on the Fenton reaction. The control reaction mixture contained 0.1 M 5,5-dimethyl-1-pyrroline N-oxide (DMPO), 0.2 mM H 2 O 2, 0.2 mM FeSO 4( NH 4)2 SO 4, and 40 mM sodium phosphate buffer (pH 7.4). Upon the addition of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Cinnamon in Goreisan and Baicalin in Sho-saikoto have also been reported to inhibit the Fenton reaction catalysed by copper or iron. ( 40 , 41 ) These may be the chemicals responsible for the effectiveness of Saireito. In ESR studies, Goreisan played a major role.…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamon in Goreisan and Baicalin in Sho-saikoto have also been reported to inhibit the Fenton reaction catalysed by copper or iron. ( 40 , 41 ) These may be the chemicals responsible for the effectiveness of Saireito. In ESR studies, Goreisan played a major role.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidation and iron chelation properties of baicalin may be related to the following reasons: baicalin promotes the transfer of electrons from Fe 2+ to dissolved oxygen, so that most of the Fe 2+ is transformed into Fe 3+ , subsequently inhibiting the formation of hydroxyl radicals ( Nishizaki and Iwahashi, 2015 ). In addition, baicalin positively regulates the expression of divalent metal transporter 1 and negatively regulates the expression of ferroportin 1, which reduces the accumulation of iron in different brain regions ( Xiong et al, 2012 ; Guo et al, 2014 ).…”
Section: Progress In the Research Regarding Flavonoids For The Treatment Of Iron Overloadmentioning
confidence: 99%
“…According to the most recent study, the excessive production of ROS is important to induce ferroptosis (17). Excessive levels of iron induce oxidative stress via Fenton and redox reactions, resulting in increased production of ROS (35). Therefore, we examined the effect of Huaier on ROS production and found that Huaier upregulated ROS levels in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 96%